Variations in mood states among Brazilian air force pilots: a crossover analysis between operational and aerobatic flight missions - Santana, Wilian de Jesus; Pivetta, Gilberto Pires; Da Silva, Carlos Eduardo Rosa; Campos, Fábio Angioluci Diniz; Farinatti, Paulo; Almeida, Gustavo; Verame, Adriano da Silva; Brandão, Regina; Figueira Junior, Aylton J. (Frontiers in Physiology, 2025)
BackgroundAerobatic flight maneuvers expose military pilots to a confluence of physiological and psychological stressors—including sustained G-forces, vestibular disorientation, and neuromuscular fatigue—that may acutely modulate emotional states and compromise cognitive performance. However, the differential psychometric impact of routine operational flights versus high-intensity air demonstrations remains poorly characterized.PurposeTo examine and compare mood state fluctuations elicited by distinct aerial mission profiles—operational maintenance (OM) flights and aerobatic demonstrations (AD)—within a specialized military pilot cohort.MethodsIn this within-subject, crossover experimental design, nine elite male aviators (mean age: 32.1 ± 1.8 years) from the Brazilian Air Force Air Demonstration Squadron (EDA), each with >1,000 cumulative flight hours, were assessed across two mission contexts. Mood states were measured pre- and post-flight using the Brunel Mood Scale (BRUMS), which evaluates six psychological dimensions: tension, depression, anger, vigor, fatigue, and confusion. Paired comparisons were conducted using the Wilcoxon signed-rank test (α = 0.05).ResultsOM flights were associated with a statistically significant increase in depression scores post-flight (p = 0.031), alongside a non-significant trend toward decreased tension (p = 0.098). Other subscales showed no statistically significant variation, though intra-individual variability was observed.ConclusionEmotional reactivity among high-performance military pilots varies according to mission typology. Incorporating continuous affective monitoring and routine psychological assessments may bolster both operational readiness and mental health preservation in high-demand aviation environments.